2021
DOI: 10.2147/ott.s334213
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Neoadjuvant Alectinib in Pulmonary Invasive Mucinous Adenocarcinoma with ALK Rearrangement: Case Report and Literature Review

Abstract: Background: Pulmonary invasive mucinous adenocarcinoma (IMA) is a rare variant of lung adenocarcinoma that rarely shows anaplastic lymphoma kinase (ALK) rearrangement. Alectinib (tyrosine kinase inhibitors) has been listed as category 1 recommendations for advanced ALK + NSCLC first-line therapy due to low toxicity and excellent efficacy, and its median progression-free survival is 34.8 months. Here, we report a case of a patient with ALK-rearranged lung IMA who showed favorable results to neoadjuvant alectini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Previous clinical trials have already verified the availability of EGFR and ALK inhibitors neoadjuvant targeted therapy in the disease control and pathological downstaging for early-stage NSCLC patients harboring the corresponding mutation, and some case reports also observed that target therapy provided effective radiologic and pathologic response in ALK , RET and ROS1 -positive resectable NSCLC patients ( 3 , 6 , 13 15 ). MET ex14m is an independent oncogenic driver occurring in 2.8% of resected stage I-III NSCLC patients ( 16 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous clinical trials have already verified the availability of EGFR and ALK inhibitors neoadjuvant targeted therapy in the disease control and pathological downstaging for early-stage NSCLC patients harboring the corresponding mutation, and some case reports also observed that target therapy provided effective radiologic and pathologic response in ALK , RET and ROS1 -positive resectable NSCLC patients ( 3 , 6 , 13 15 ). MET ex14m is an independent oncogenic driver occurring in 2.8% of resected stage I-III NSCLC patients ( 16 ).…”
Section: Discussionmentioning
confidence: 91%
“…Immunohistochemistry outcomes were presented as: HE (A), TTF-1 (+) (B), NapsinA (+) (C), CK7 (+) (D), CK5/6 (-), CK (pan) (+), and Ki-67 (+, about 50%). some case reports also observed that target therapy provided effective radiologic and pathologic response in ALK, RET and ROS1-positive resectable NSCLC patients (3,6,(13)(14)(15). METex14m is an independent oncogenic driver occurring in 2.8% of resected stage I-III NSCLC patients (16).…”
Section: Discussionmentioning
confidence: 99%
“…neoadjuvant treatment did not experience treatment-related adverse effects but achieved an MPR. Taking the medical records of these two cases together with previous reports [4][5][6], neoadjuvant alectinib maybe clinically feasible.…”
Section: Discussionmentioning
confidence: 98%
“…Ten patients (91%) had R0 resection, including two cases of pCR ( 23 ). Furthermore, cases of successful neoadjuvant targeted therapy for ROS1, RET, or ALK rearrangement were reported ( 25 28 ). The prospective phase II ALNEO and NAUTIKA1 studies on neoadjuvant alectinib therapy finished enrolment, and preliminary results were reported ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%